KECERDASAN EKOLOGIS DALAM BUKU SEKOLAH ELEKTRONIK MATA PELAJARAN BAHASA INDONESIA SMP - Sarwiji Suwandi; Ahmad Yunus; Laili Etika R (LITERA, 2016)
This study aims to explain ecological intelligence contents in electronic Indonesian language course books for junior high school (JHS) students. The methods in the studywere literature review and content analysis. The ecological intelligence contents  in thebooks include: (1) identifying ecosystem components; (2) comprehending the functionsand uses of the components; (3) understanding environmental management systems; (4)understanding environmental values which comprise local wisdom and religious andnormative values; (5) showing concern about environmental destruction and pollution; (6)adapting behavior to the environment; (7) solving problems arising from environmentalimpacts, either individually or collectively; (8) managing/preserving natural resources;and (9) exploiting the environment positively. The ecological intelligence contents are stilldominated by the cognitive aspect and have not emphasized the comprehension, valueinternalization, and application aspects.